"Water Education" - an Educational and Legal Need - Krajewski, Piotr Wacław; Krajewska, Anna Zofia (Journal of Modern Science, 2025)
Objectives Environmental education about water for ethical and responsible water consumption aims to: promote awareness of the water crisis as a global environmental problem; To spread and share knowledge about local water availability; promoting social and ethical awareness of water as a human right and a common heritage to be protected for future generations; determining ethical conduct and responsible use of water; preparing children and young people to share responsibility and participation in the management and protection of water as a common good. Material and methods This goal can be achieved with the use of traditional educational methods after collecting and developing published popular science and specialist materials and materials available on the Internet. Results Joint work (with the teacher) and individual work, preceded by a query and processing of source materials and ending with the presentation of the results of work to the group, is of an extremely interdisciplinary nature. It draws attention to current and important ecological problems and can be an example of combining theoretical educational goals with active learning about them and looking for practical solutions for them. Conclusions The implementation of this thematic area is to lead to the initiation of new attitudes and behaviors in young people, awakening the ability to analyze reality, and finally, to taking spontaneous actions within the scope of their own abilities or joining their organized forms.